Endoscopic removal of nasal septum chondrosarcoma in paediatric patient - Abu Bakar, Muhammad Nasri; Ramli, Rosdi; Salahuddin, Zulkiflee; Mohamad, Irfan (Elsevier, 2014)
Chondrosarcomas of the head and neck are uncommon malignant tumours of nonepithelial origin. They rarely occur in paediatric age group. The treatment is mainly surgical and adjuvant therapy is only reserved to certain cases. We report a boy with progressive history of nasal obstruction and epistaxis. Nasal endoscopy revealed a mass arising from nasal septum. Endoscopic excision of the tumour was successfully done followed by radiotherapy. Endoscopic excision of chondrosarcoma of the nasal septum in its early stage should be considered for better outcome.